Assessment on the Effectiveness of Pseudo-Narcotics Training Aids to Candidate Coast Guard Detection Dogs - Abas, Joselle Luz A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined the effectiveness of pseudo-narcotic training aids in replicating the scent profiles of real narcotic substances, specifically marijuana and methamphetamine hydrochloride (shabu), for training Coast Guard K9 narcotics detection dogs. A mixed-methods approach was used, combining performance evaluations of ten handler-dog teams with focus group discussions involving instructors, evaluators, and handlers. Findings revealed that dogs trained with pseudo-narcotics achieved perfect detection rates in most conditions and performed comparably to those trained with real substances, even in distraction-rich environments. However, real narcotics generally produced faster detection time and fewer false indications. Statistical analysis confirmed differences in detection speed without distractions, but no significant differences under distracting conditions. Thematic analysis highlighted six key factors: use in refresher training, the need for initial imprinting with real substances, legal and logistical benefits, environmental influences, scent differentiation challenges, and the role of evolving training technologies. The study concludes that pseudo-narcotics are effective adjuncts for maintenance and broad deployment. However, they cannot fully substitute for real narcotics in foundational imprinting. This study provides evidence that pseudo-narcotics can complement, but not fully replace, real narcotics in Coast Guard K9 training.